KERJASAMA INDONESIA-USAID DALAM MENANGGULANGI TUBERKULOSIS DI INDONESIA PERIODE 2013-2016 - Ayu Dwi Septiany, - (2018)
This study examines the working relationship between Indonesia-USAID in tackling Tuberculosis in Indonesia period 2013-2016. Tuberculosis spread in Indonesia has increased every year, so this has led to the formation of cooperation between Indonesia and the United States through an international institution, USAID, in tackling cases of Tuberculosis in Indonesia. This study raises the question "How Implementation of Indonesia-USAID Cooperation in Tackling Tuberculosis in Indonesia Period 2013-2016?". To be able to answer questions using theories and concepts such as The Theory of International Cooperation, Theory of International Organizations, Concepts of Technical Assistance and Concepts of Human Security. This method uses descriptive qualitative method, which focuses on the use of primary data derived from interviews and official documents and other secondary data to support the discussion and understanding of this research. Based on data analysis conducted, it is concluded that the cooperation between Indonesia and USAID provides funding and technical assistance through Community Empowerment Program of People Against Tuberculosis which aims to increase awareness of prevention and control of Tuberculosis, as well as to prevent and to the national Tuberculosis program , by implementing various activities such as, Health supply side, Health promotion, Management, and Sustainability